2023
DOI: 10.1038/s41467-023-41459-4
|View full text |Cite
|
Sign up to set email alerts
|

Ustilago maydis PR-1-like protein has evolved two distinct domains for dual virulence activities

Yu-Han Lin,
Meng-Yun Xu,
Chuan-Chih Hsu
et al.

Abstract: The diversification of effector function, driven by a co-evolutionary arms race, enables pathogens to establish compatible interactions with hosts. Structurally conserved plant pathogenesis-related PR-1 and PR-1-like (PR-1L) proteins are involved in plant defense and fungal virulence, respectively. It is unclear how fungal PR-1L counters plant defense. Here, we show that Ustilago maydis UmPR-1La and yeast ScPRY1, with conserved phenolic resistance functions, are Ser/Thr-rich region mediated cell-surface locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Although direct evidence is still lacking for the role of sterol binding of CAP domain during infection of fungal pathogens, study in tobacco PR-1 revealed that plants could inhibit pathogen growth through the sequestration of sterol from pathogens by PR-1 protein [42]. In U. maydis, UmPR-1La not only participates in sensing phenolics and eliciting hyphal-like formation, but also releases CAPE-like peptides to subvert plant immunity [31]. Besides, pathogens evolved specific clade of CAP protein lacking the conserved cysteine residues required for intramolecular disulfide bridges, and were proposed to bind novel ligands [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although direct evidence is still lacking for the role of sterol binding of CAP domain during infection of fungal pathogens, study in tobacco PR-1 revealed that plants could inhibit pathogen growth through the sequestration of sterol from pathogens by PR-1 protein [42]. In U. maydis, UmPR-1La not only participates in sensing phenolics and eliciting hyphal-like formation, but also releases CAPE-like peptides to subvert plant immunity [31]. Besides, pathogens evolved specific clade of CAP protein lacking the conserved cysteine residues required for intramolecular disulfide bridges, and were proposed to bind novel ligands [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Cytospora chrysosperma, CcCAP1 is required for the suppression of immunity in poplar plants [29]. So far, only a few studies demonstrated that the CAP proteins are required for lipid export and sterol binding in fungus [30], and a recent study in Ustilago maydis uncovered that it could hijack maize cathepsin B-like 3 (CatB3) to cleave the PR1-like protein UmPR-1La, leading to the release of functional CAPE-like peptides for the interruption of plant CAPE mediated immunity [31]. However, whether these CAP proteins function could target other ligands or proteins during infection remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2C ). Nevertheless, the importance of PR1 in plant immunity is evident, reflected by the fact that pathogen effectors target PR1 (Breen et al, 2016 ; Li et al, 2022 ; Lin et al 2023 ). Other PR proteins such as PR2, PR5, defensin (PR12), and thionin (PR13) appear to have an activity to disrupt pathogen cell walls and the plasma membrane (Boccardo et al, 2019 ; Rayapuram et al, 2008 ; Zribi et al, 2021 ).…”
Section: Molecule-mediated Pathogen Suppressionmentioning
confidence: 99%